Optimization of Anguilla bicolor oxygen consumption in alkalinity culture media - Andre Rachmat Scabra; Tatag Budiardi (Universitas Muhammadiyah Malang, 2020)
One potential aquaculture commodity that can be developed is Anguilla bicolor. One effort that can be conducted to maximize the life and growth of A. bicolor by manipulating water quality through alkalinity parameters. Alkalinity is a buffer capacity for changing in water pH, and osmotic pressure of water. Alkalinity levelss in culture media can be managed by the addition of calcium carbonate (CaCO3), calcium oxide (CaO), or calcium hydroxide (CaOH) with a certain dose to the culture media. This study aimed to determine the effect of alkalinity on aquaculture media based on the level of oxygen consumption (OC) that related to growth value. This research was conducted with an experimental design using a completely randomized design (CRD) with four treatments, namely the addition of CaCO3 to maintenance media with different doses (A, 0 mg/L; B, 50 mg/L; C, 100 mg/L; D, 150 mg/L). The results showed that the treatment B (50 mg / L) showed an OC value (0.15 mgO2/g/h) and an optimal Growth Rate (GR) (3.75 g/day), while the Survival Rate (SR) parameter, the treatment had no significant effect. The conclusion was 50 mg/L of calcium carbonate (CaCO3) having the optimum alkalinity level in A. bicolor culture media. At the additional dose of CaCO3, the growth value (GR), and the level of eel fish oxygen consumption were optimal.